Mechanism for Needs Planning and Budgeting for Regional Property at Public Works, Spatial Planning and Land Department of Banjar District - Pratami, Oktavina Yoka; Respati, Novita WeningTyas (AJAR, 2026)
This study aims to analyze the consistency of the mechanism for the needs planning and budgeting of regional assets at the Department of Public Works, Spatial Planning and Land in Banjar Regency for the fiscal year 2022 in relation to applicable regulations. A descriptive qualitative approach was employed, involving Public Works, Spatial Planning and Land Department employees as key informants. Data were collected through interview techniques and documentation studies, then analyzed through stages of data reduction and presentation. The findings reveal that although most procedures have complied with regulatory provisions, administrative constraints persist due to a long-standing pattern of neglect in asset management. The novelty of this research lies in the identification of systemic problems in the form of prolonged administrative neglect, which constitutes the main obstacle to the effectiveness of the Regional Asset Needs Plan. Thus, the issues encountered are not merely technical budgetary constraints, but rather structural and governance-related problems. The implications of these findings emphasize that without transformation of organizational culture and strict standardization of procedures, asset planning will remain a mere formality lacking accurate real data. This study is expected to serve as a strategic reference for the Public Works, Spatial Planning and Land Department in optimizing more accountable regional assets governance.